Literature Review: Waktu Tunggu Obat di Instalasi Farmasi Rumah Sakit - Amir, Kemal; Tulak Rerung, Lola' (Journal of Pharmacy Tiara Bunda, 2023)
Prescription service is the patient's final point in the health care process. Therefore, the hospital must pay attention to the processing time for patient prescription services. The waiting time for prescription services is divided into two, namely finished drugs with a time of ≤ 30 minutes and concoction drugs ≤ 60 minutes. This literature review study aims to determine the waiting time for drugs in hospital pharmacy installations. The method used is the Literature Review approach. This study uses a descriptive method in the form of a literature review. A literature search of research journals, scientific articles and journal reviews through google schoolar, researchgate, and garuda portal. This Literature Review study was obtained from research article searches of the last 10 years. 10 journals that meet predetermined inclusion and exclusion criteria. Based on the results of the Literature Review that was carried out, it was found that 7 journals were in accordance with the minimum service standards of the hospital. While 3 journals did not meet the minimum hospital service standards.